On Conjugate Symplecticity of Multi-Step Methods (Journal of Computational Mathematics, 2000)
In this paper, we solve a problem on the existence of conjugate symplecticity of linear multi-step methods (LMSM), the negative result is obtained.
Keywords: Conjugate symplecticity; Multi-step method.